Adequacy of the law in protecting the rights of adopted children in Malaysia - Che Soh @ Yusoff, Roslina; Abdul Hak, Nora; Md Hashim, Noraini; Md Said, Muhamad Helmi (Universitas Muhammadiyah Yogyakarta, 2017)
Adoption is one of the means to protect children who have been deprived of parental care. The United Nation Convention on Rights of Child guaranteed such protection and as in other action con- cerning children, the principle of the best interest of the child must be primarily considered by the State parties when dealing with the process of adoption. In Malaysia, adoption process is governed under two main legislations, i.e. Adoption Act 1952 and Registration of Adoption Act 1952. This paper addresses the extent of these legislations and practices of the Court in Malaysia in ensuring the best interest of the child is guaranteed when dealing with adoption procedures and the protection provided after the adop- tion. One of the main issues to be highlighted is concerning the citizenship of the adopted child, particu- larly in a case where the child is not from Malaysia. Does the law give equal protection as provided to the adopted child born in Malaysia? This paper uses a qualitative data collection method where in-depth document analysis is carried out. Primary sources such as the Acts, Regulations, court orders and decision are scrutinised. On the other hand, secondary sources that are studied include law reports, law reviews and legal periodical articles. The study is significant as it addressed crucial concerns raised in reference to the current laws relating to the protection of adopted children in Malaysia. The paper ends with some possible recommendations that may spur improvement to the present legislations in ensuring that the rights of adopted children in Malaysia are duly protected.